NUTRITIONAL TACTICS FOR BASKETBALL - Escribano, Ignacio (Sport- és Egészségtudományi füzetek, 2026)
Optimal nutrition in basketball hinges not only on choosing the right types of nutrients – specifically carbohydrates and proteins – but also on determining the correct amounts and the optimal timing of their intake. This strategic approach is crucial for effective recovery. During games, players endure intense physiological challenges. Moreover, the physical demands placed on players are shaped by intrinsic factors such as game position, player level, experience, gender, and age, as well as extrinsic factors like the frequency of matches and training sessions. These complex and varied elements demand highly precise, specific, and customized nutritional strategies.